PENGARUH KEPEMIMPINAN, KOMPETENSI, LOCUS OF CONTROL DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI PENGEMBANGAN KOMPETENSI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT ( PUPR) WILAYAH II PALEMBANG - Ulil Amri; Kartawinata Kartawinata; Ellen Sumiarni (JURNAL KOMPETITIF, 2022)
This study examines the performance of the Competency Development Center for Public Works and Public Housing (PUPR) Region II Palembang employees. The purpose of this research is to find out and prove whether there is influenceleadership, competence, locus of control and work discipline simultaneously on employee performance. The research location of the Competency Development Center for Public Works and Public Housing (PUPR) Region II Palembang on Jalan Aiptu. Karel Tubun No. 12, 17 Ilir Kec. Ilir Timur I Palembang City. The population in this study were 42 employees and the sampling technique using the census method was 42 operational employees. Data collection techniques through the distribution of closed questionnaires. The research data instruments were tested for validity and reliability. The analysis technique uses inferential statistics with multiple linear regression equations, then the regression coefficient, correlation coefficient and coefficient of determination are determined. Test the hypothesis through F-test and t-test both to see the effect simultaneously and partially. The significance level is 5%. Data processing media through the SPSS version 20.0 program. The results of data analysis obtained a correlation (r) between leadership, competence, locus of control and work discipline simultaneously with employee performance of 0.897 or 89.70% which means it has a significant and significant relationship while Adjusted (R2 ) of 0.783 or 78.30% variation in performance and the remaining 21.70% is explained by other factors such as compensation, work stress and work environment. Multiple linear regression equation: Ŷ= 17.037 + 0.510X1 + 0.568X2 + 0.256X3+0.229X4 + e. The results of the F-test obtained a Fhit value of 37.910 with a Sig level. 0.000, because the Sig.F value <0.05 proves that there is an influence of leadership, competence, locus of control and work discipline simultaneously on performance. The results of the t-test obtained a thit value of 3.884 with Sig.0.000 <0.05 for leadership, a thit value of 4.410 with Sig.0.000<0.05 for competence, a thit value of 2.397 with Sig.0.022 <0.05 for locus of control and a thit value of 2.589 with Sig.0.014 <0.05 for work discipline, so partially that leadership, competence, locus of control and discipline affect employee performance.Keyword: employee performance (Y), leadership (X1), competence (X2), locus of control (X3), work discipline (X4)